2015
DOI: 10.1111/1365-2478.12333
|View full text |Cite
|
Sign up to set email alerts
|

Using wavelet‐domain adaptive filtering to improve signal‐to‐noise ratio of nuclear magnetic resonance log data from tight gas sands

Abstract: A B S T R A C TIn tight gas sands, the signal-to-noise ratio of nuclear magnetic resonance log data is usually low, which limits the application of nuclear magnetic resonance logs in this type of reservoir. This project uses the method of wavelet-domain adaptive filtering to denoise the nuclear magnetic resonance log data from tight gas sands. The principles of the maximum correlation coefficient and the minimum root mean square error are used to decide on the optimal basis function for wavelet transformation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Most of the current echo signal denoising algorithms are based on noise estimation. The effectiveness of the algorithms is verified by adding Gaussian white noise during numerical simulation and adjusting the parameters to denoise [7,9]. However, the parameters obtained by the above way will cause the noise characteristics to be mismatched when applied to logging data, making it difficult to get great denoising performance.…”
Section: Noise Characteristics Of Echo Signalmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the current echo signal denoising algorithms are based on noise estimation. The effectiveness of the algorithms is verified by adding Gaussian white noise during numerical simulation and adjusting the parameters to denoise [7,9]. However, the parameters obtained by the above way will cause the noise characteristics to be mismatched when applied to logging data, making it difficult to get great denoising performance.…”
Section: Noise Characteristics Of Echo Signalmentioning
confidence: 99%
“…Chen et al identified the singular values in terms of the correlation between the FID and the reference data, and then the radio frequency interference and noise were suppressed by setting the corresponding singular values to zero [8]. Xie et al proposed a method of waveletdomain adaptive filtering to denoise the NMR log data from tight gas sands [9]. Cai and Xiao combined generalized S transform and SVD to filter NMRL signal [10].…”
Section: Introductionmentioning
confidence: 99%